Comparison of perioperative outcomes of robotic vs. laparoscopic partial nephrectomy for renal tumors with a RENAL nephrometry score ≥7: A meta-analysis - Jiang, Yu-Li; Yu, Dong-dong; Xu, Yang; Zhang, Ming-Hua; Peng, Fu-Sheng; Li, Peng (Frontiers in Surgery, 2023)
Introduction To compare the perioperative outcomes of robotic partial nephrectomy (RPN) vs. laparoscopic partial nephrectomy (LPN) for complex renal tumors with a RENAL nephrometry score ≥7. Methods We searched PubMed, EMBASE and the Cochrane Central Register for studies from 2000 to 2020 to evaluate the perioperative outcomes of RPN and LPN in patients with a RENAL nephrometry score ≥7. We used RevMan 5.2 to pool the data. Results Seven studies were acquired in our study. No significant differences were found in the estimated blood loss (WMD: 34.49; 95% CI: −75.16–144.14; p = 0.54), hospital stay (WMD: −0.59; 95% CI: −1.24–0.06; p = 0.07), positive surgical margin (OR: 0.85; 95% CI: 0.65–1.11; p = 0.23), major postoperative complications (OR: 0.90; 95% CI: 0.52–1.54; p = 0.69) and transfusion (OR: 0.72; 95% CI: 0.48–1.08; p = 0.11) between the groups. RPN showed better outcomes in the operating time (WMD: −22.45; 95% CI: −35.06 to −9.85; p = 0.0005), postoperative renal function (WMD: 3.32; 95% CI: 0.73–5.91; p = 0.01), warm ischemia time (WMD: −6.96; 95% CI: −7.30–−6.62; p < 0.0001), conversion rate to radical nephrectomy (OR: 0.34; 95% CI: 0.17 to 0.66; p = 0.002) and intraoperative complications (OR: 0.52; 95% CI: 0.28–0.97; p = 0.04). Discussion RPN is a safe and effective alternative to LPNs for or the treatment of complex renal tumors with a RENAL nephrometry score ≥7 with a shorter warm ischemic time and better postoperative renal function.